Relationship Between Health Literacy and Re-emerging Elephantiasis in Aceh Barat - Danvil Nabela; Dian Fera; Susy Sriwahyuni; Agusriati Muliyana (Universitas Teuku Umar, 2021)
Filariasis is an infectious disease caused by filarial worms if it is not fast, it will experience permanent disability, it occurs when a chronic condition occurs when the feet and hands become swollen, in that condition it is called elephantiasis (elephant leg). West Aceh Regency is one of the districts which has the highest number of filariasis cases, which continues to increase from 9 cases in 2015 to 15 cases in 2017. Many factors are suspected to be the cause of elephantiasis including knowledge, behavior, physical home environment, socialization of counseling to health workers. health literacy with the re-emergence of elephantiasis in West Aceh Regency in 2019. This study used a quantitative study to determine the risk of elephantiasis using Matched Case Control. The population of cases in this study were people who suffered from elephantiasis in the district of West Aceh. Given the population (N), namely patients with filariasis <100, the sample in this study was the total population using a ratio of 1: 3, so the number of samples in this study was 60 people consisting of 15 cases and 45 people as controls. The results showed that the disease re-emerged. Elephantiasis in West Aceh Regency in 2018 was related to health literacy (p = 0.003)